De tolk als respeaker: een kwestie van training - van der Veer, Bart (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2021)
As a result of political decisions, all Dutch-spoken television programmes that are broadcast by the Flemish Broadcasting Company (VRT) should be provided with subtitles for the deaf and hard of hearing by the year 2010. In order to meet these high expectations, the VRT is constantly improving and changing its subtitling techniques, as are other broadcasting companies worldwide. One of the main areas of change concerns the technique of live subtitling, i. e. real time subtitling of live television programmes. This type of subtitling has definitely benefited from the use of modern speech recognition software. Live subtitling, therefore, requires not only technical skills but also excellent ‘respeaking’ skills that are reminiscent of the skills of conference interpreters. The central question in the first part of this pa- per is to what extent ‘re-speaking’ is related to simultaneous (and other forms of) interpreting: is a good interpreter automatically a good re- speaker? In the second part, I adopt a didactic point of view in order to investigate the teaching aspects of real time subtitling skills: the conclusion is that it is best included in an education programme for conference interpreters